Implementation Of The Talking Stick Learning Model Used By Koper Sebeni Media - Anjarsari, Iis; Fayeldi, Trija; Pranyata, Yuniar Ika Putri (RAINSTEK: Jurnal Terapan Sains dan Teknologi, 2024)
The use of media can increase clarity and interest in the learning process, increase learning motivation, and make it easier to understand the material. The aim of this research is to determine the talking stick learning model that can improve student learning outcomes in comparative material in class VII Pagak Islamic Middle School with the help of the Koper Sebeni media. This classroom action research was carried out using qualitative methodology. The steps in the process are preparation, action, observation, and reflection. The flow model is used to analyze the data obtained, which includes data reduction, data presentation, and drawing conclusions. The research results showed that from cycle 1 to cycle 2 student learning outcomes increased. The percentage of completion of the final exams for cycles 1 and 2 was 83.33% and 91.67% respectively, which shows an increase in the proportion of students by 8.33%. Thus it can be said that the use of the Koper Sebeni media combined with the talk stick learning strategy can improve student learning outcomes. So that most students have the opportunity to answer questions, future researchers must spend sufficient time on the talking stick learning model.